Dinamika Fungsi Teritorial Manusia pada Ruang Publik di Kampung Nelayan Sejahtera Kota Bengkulu - Salsabila Melka Rifti; Dewi Septanti; Ima Defiana (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
The development of public activity spaces in traditional fishing communities due to urbanization and the growth of tourism has led to changes in existing territories. This requires them to adjust to these changes. This research aims to understand how fishing communities maintain their territories through spatial practices, social interactions, and territorial definitions after the changes. The research method used is qualitative phenomenology, to explore the organization of social interaction, identity, security, and territorial stimulation of the community in public activity spaces. Through observations and interviews, it was found that fishermen's territoriality, in addition to functioning as a defense, also plays an important role in strengthening social relations. The unique factors that shape the concept of fishermen's territoriality, namely dependence on income sources, egalitarian social structure, and a strong spirit of gotong royong, produce a concept of spatial interaction that is different from other neighborhoods.